2006
DOI: 10.1007/s00406-006-0660-8
|View full text |Cite
|
Sign up to set email alerts
|

Tranylcypromine

Abstract: The irreversible inhibitor of monoamine oxidase, tranylcypromine, is a potent antidepressant, but its use is limited to special indications due to side effects and dietary restrictions. The antidepressant action of tranylcypromine is not completely explainable by its effects on monoamine oxidase. Tranylcypromine also leads to an increase in brain trace amines, which are believed to play a key role in the pathophysiology of depression. It also affects other pathophysiological pathways associated with depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…MC3935 was synthesized based on the scaffold of the nonselective and irreversible monoamine oxidase (MAO) inhibitor tranylcypromine (TCP) [29,42]. Tranylcypromine is a mechanism-based suicide inhibitor of MAO and LSD1; it covalently binds to the FAD cofactor embedded within the protein, thus abolishing enzymatic catalysis [43].…”
Section: Discussionmentioning
confidence: 99%
“…MC3935 was synthesized based on the scaffold of the nonselective and irreversible monoamine oxidase (MAO) inhibitor tranylcypromine (TCP) [29,42]. Tranylcypromine is a mechanism-based suicide inhibitor of MAO and LSD1; it covalently binds to the FAD cofactor embedded within the protein, thus abolishing enzymatic catalysis [43].…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that LSD1 plays a crucial role in fetal γ-globin silencing and that an LSD1 inhibitor, TCP, can enhance HbF synthesis. TCP has been widely used as an antidepressant with manageable side effects; it exerts its antidepressive effect by elevating serotonin levels 18 and does not seem to have cytotoxic or mutagenic effects. Although it was recently reported that LSD1 inhibition by RNAi in mice can cause hematopoietic defects 19 , hematological toxicity has not been associated with TCP in humans except in rare cases of transient thrombocytopenia attributable to overdosing 20 .…”
mentioning
confidence: 99%
“…The new findings in the present study are: 1) endogenous PGI 2 production mediates nonneuronal COX-2-dependent neuroprotection; 2) PGI 2 is produced by a subset of infiltrating neutrophils that populate the lesion core in response to excitotoxin administration; and 3) PGI 2 can exert neuroprotective effects by directly reducing NMDA-mediated excess calcium influx. There is a significant clinical implication resulting from the observation that endogenous PGI 2 has a neuroprotective effect: the PGIS inhibitor tranylcypromine is also an inhibitor of monoamine oxidase, and this drug is used clinically as an antidepressant;20 consequently, patients on tranylcypromine therapy may have an increased risk of exacerbated neural damage in response to acute brain injury.…”
Section: Discussionmentioning
confidence: 99%